TEAL application in training TVET graduates to solve the unemployment problem - Hassan, Nur Farha; Puteh, Saifullizam; Muhamad Sanusi, Amanina; Megat Salleh, Nan Nurul Hidayah (American Scientific Publisher, 2018)
In today’s job market, graduates are expected to have various types of knowledge and skills related to the jobs applied for. Employers prefer graduates equipped with knowledge in practical technology so that they can help improve the product or management quality of the company. This study focuses on the issues and problems of TVET graduates in securing employment in the industrial sector. This study utilised semi-structured interviews as an instrument to collect the relevant information. The respondents were and are experts in the fields of engineering and technology. The interviews were conducted to identify the relevant terms in the application of Technology Enabled/Enhanced Active Learning (TEAL) so that the institutions can use the information to produce graduates that meet the requirements of the industry. Recordings of the interview sessions were transcribed; issues and problems were then identified. The results of the analyses show that employers in the industry today need quality graduates who possess practical knowledge and skills applicable to the real work in the industrial sector.